Regioselective formation of highly functionalised heterofullerenes: Pentamalonates of RC59N involving an octahedral addition pattern - Hauke, Frank; Hirsch, Andreas; Hauke, Frank (Chemical Communications, 2001)
The treatment of monomeric azafullerene derivatives RCN with an excess of diethyl bromomalonate in the presence of DBU and dimethylanthracene leads to the regioselective formation of azafullerene pentamalonates with an octahedral C symmetrical addition pattern.